Heritage-Based Local History Education: The Tjilik Riwut House and the Development of Students’ Historical Consciousness in Palangkaraya - Yusnani Novelianty; Miftahuddin Miftahuddin; Dede Wahyu Firdaus; Rahmat Fauzi; Reza Renggana Hamdani (Diakronika, 2025)
Low student motivation in history learning is a challenge for teachers. History lessons aim to foster a spirit of nationalism and shape students' character. Conventional and monotonous learning is one of the causes. To address this challenge, innovative methods are needed in utilizing learning resources. The Tjilik Riwut House Cultural Heritage in Palangkaraya City has the potential for historical character value that can be integrated as a source of history learning, especially local history. This study aims to explore the Tjilik Riwut house as a source of local history and character values from Tjilik Riwut in 21st-century learning. This research is included in qualitative research using observation, interview, and documentation techniques. Data is also supported by archives, site profiles, photographs and relevant documents. The collected data is then reduced by sorting the data to find truly valid data. After the reduction stage, the data presentation stage is carried out including a structured summary of the framework of thought which will later lead to the final stage of conclusion. The results show that the Tjilik Riwut house cultural heritage has the potential as a local historical source containing data on the life journey of Mr. Tjik Riwut and his role in defending the Palangkaraya region from the Dutch. Character education can be learned through the struggle of Mr. Tjilik Riwut. The novelty of this research lies in the use of the Tjilik house as a source of local history learning. The conclusion of the study confirms that the use of the Tjilik Riwut house cultural heritage as a local historical source is effective in fostering a spirit of nationalism, responsibility, social obedience, and pluralism among high school students in Palangkaraya City. Keywords: cultural heritage, character education, Tjilik Riwut house, local history, historical sources